ANALYSIS OF POLITENESS STRATEGIES OF JAPANESE WOMAN IN GEISHA MOVIE - Sri Sugiharti (CAHAYA PENDIDIKAN, 2016)
This study analyzed of the Geisha  movie. This study used brown and Levinson theory of positive politeness (1987). The data of this study use the script of  “Geisha” movie. The data found,  the writer found out the data 111 of the  “Geisha” movie used of positive politeness as suggested by Brown and Levinson (1987).  The data applied by using qualitative research.. The objective of the study is to  identify the positive politeness Strategy and negative politeness Strategy. The result of the study is  the positive politeness Strategy 1, 10 times ( 4,87% ), Strategy 2,3 times ( 1,46% ),Strategy 3, 4 times (1,95%  ), Strategy 4, 20 times (9,75  ),Strategy 5, 4 times (1,95%  ), Strategy 6, 12 times (5,85% ), Strategy 7,  4 times ( 1,95% ), Strategy 8, 0 times ( 0 ), Strategy 9, 4 times ( 1,95% ), Strategy 10, 3 times ( 1,46% ), Strategy 11, 6 times (2,92%  ), Strategy 12, 13 times (6,34% ), Strategy 13, 20 times (9,75%  ), Strategy 14, 3 times (1,46%  ), and Strategy 15, 14 times ( 6,82% ). Therefore, the positive politeness mostly frequently was strategy 13 used in the Geisha. Keywords: Positive politeness, Japanese woman, and Geisha